2017
DOI: 10.1002/app.45573
|View full text |Cite
|
Sign up to set email alerts
|

Polymer/boehmite nanocomposites: A review

Abstract: Boehmite is an aluminum oxyhydroxide [AlO(OH)] which is preferentially used as precursor for the production of (transition) aluminum oxides. Boehmite alumina (BA) nanoparticles are available in various morphologies due to versatile synthesis routes, which are briefly introduced. The peripheral hydroxyl groups of BA offer manifold functionalization possibilities for tailoring the dispersion and filler/matrix adhesion properties. The incorporation of BA nanofillers, with and without surface treatments, may yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 168 publications
2
52
0
Order By: Relevance
“…Peaks corresponding to Au are also present since all specimens were covered with a thin Au layer prior to SEM inspection. A representative TEM picture of the same type of BA used for the preparation of the nanocomposites of the present study with (120) crystallite mean size 80 nm can be found elsewhere …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Peaks corresponding to Au are also present since all specimens were covered with a thin Au layer prior to SEM inspection. A representative TEM picture of the same type of BA used for the preparation of the nanocomposites of the present study with (120) crystallite mean size 80 nm can be found elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…Boehmite alumina (BA) is widely used as a filler for the preparation of nanocomposites since it can be easily dispersed in various polymers. Specifically, despite the fact that an improved distribution can be achieved by various surface treatments, BA's polar nature ensures a uniform dispersion in most polymers without the need for any modification . BA forms a complex structure with surface hydroxyl groups (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5] Among them, b-form crystal presents different characteristic from its other counterparts, such as low crystal density, low melting temperature, and low fusion enthalpy, but remarkably improved impact strength and toughness. [6][7][8] Though b-form crystal of iPP is difficult to be obtained under normal processing conditions (only special crystallization procedures, such as, crystallization with specific nucleation agents, [9,10] under temperature gradient, [11] or with acid-corroded glass fiber (GF) [12,13] ), it has been found that sheared iPP melt well encourages the formation of b-form crystal. [14][15][16][17][18] Meanwhile, an effective research model via pulling fiber in the iPP melt to investigate the mechanism of shear-induced b-form crystal has been extensively employed.…”
Section: Introductionmentioning
confidence: 99%